Staphylococcus Alpha-Toxin Action on the Rabbit Iris: Toxic Effects and Their Inhibition. (August 2015) - Arana, Angela M.; Bierdeman, Michael A.; Balzli, Charles L.; Tang, Aihua; Caballero, Armando R.; Patel, Rupesh; O'Callaghan, Richard J.
Abstract Purpose: Staphylococcus aureus infection of the anterior chamber can occur after cataract surgery, causing inflammation and extensive damage to the iris. Alpha-toxin, the most potent S. aureus corneal toxin, was tested as a possible mediator of damage to the iris, and alpha-toxin anti-serum and a chemical toxin inhibitor were tested as potential pathology-reducing agents. Methods: The hemolytic activity of alpha-toxin and its inhibition by a chemical inhibitor or anti-serum were quantified in vitro. Purified alpha-toxin, heat-inactivated toxin, or alpha-toxin plus normal serum, alpha-toxin anti-serum, or the chemical inhibitor, methyl-β-cyclodextrin-cholesterol (CD-cholesterol), was injected into the rabbit anterior chamber. Pathological changes were photographed, quantified by slit-lamp examination (SLE) scoring, and further documented by histopathological analysis. Results: At five hours post-injection, eyes injected with alpha-toxin or heat-inactivated toxin had a mean SLE score of 7.3 ± 0.59 or 0.84 ± 0.19, respectively. Active toxin caused moderate to severe iris edema, severe erosion of the iris, and mild to moderate fibrin accumulation in the anterior chamber. Alpha-toxin plus anti-serum or CD-cholesterol, in contrast to alpha-toxin alone, caused less iris edema and epithelium sloughing as well as significantly lower SLE scores than eyes receiving alpha-toxin alone (p ≤ 0.019). Conclusion: Alpha-toxin caused extensive iris damage and inflammation, and either anti-alpha-toxin anti-serum or CD-cholesterol was able to significantly reduce toxin-mediated damage and inflammation.